Use Of The Patiayam Museum As A Source For Learning History At Mejobo 1st State High School In The Principal Period Of History Main Material - Utomo, Santiko (Indonesian Journal of History Education, 2016)
Learning activities are a complex process that involves making learning activities active, innovative, and practical and creating a pleasant learning atmosphere. The limited source of learning history makes the teacher use the Patiayam museum as a source of learning history. The objectives of this study are (1) to find out the extent to which the Patiayam Museum is a source of historical learning, (2) to know the readiness of the Patiayam Museum to use the museum as a source of historical learning, (3) to find out what constraints faced by Mejobo 1 High School Patiayam Museum in utilizing the Patiayam museum as a source of learning history. This research method uses historical qualitative research, where the data sources used are objective, systematic, accurate, and authentic, which can be justified. The results of the study: (1) historical learning, especially in the subject matter of the pre-trial history at Mejobo 1 High School, was carried out by utilizing the Patiayam Museum as a learning resource. (2) Patiayam Museum provides learning facilities through fossils, artifacts, touch screens, and museum officers who explain collections; (3) constraints faced by students, teachers, and museums related to Patiayam museum utilization activities.